(x)(x+1)(x+2)=36

Simple and best practice solution for (x)(x+1)(x+2)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x)(x+1)(x+2)=36 equation:


Simplifying
(x)(x + 1)(x + 2) = 36

Reorder the terms:
x(1 + x)(x + 2) = 36

Reorder the terms:
x(1 + x)(2 + x) = 36

Multiply (1 + x) * (2 + x)
x(1(2 + x) + x(2 + x)) = 36
x((2 * 1 + x * 1) + x(2 + x)) = 36
x((2 + 1x) + x(2 + x)) = 36
x(2 + 1x + (2 * x + x * x)) = 36
x(2 + 1x + (2x + x2)) = 36

Combine like terms: 1x + 2x = 3x
x(2 + 3x + x2) = 36
(2 * x + 3x * x + x2 * x) = 36
(2x + 3x2 + x3) = 36

Solving
2x + 3x2 + x3 = 36

Solving for variable 'x'.

Reorder the terms:
-36 + 2x + 3x2 + x3 = 36 + -36

Combine like terms: 36 + -36 = 0
-36 + 2x + 3x2 + x3 = 0

The solution to this equation could not be determined.

See similar equations:

| 8x-(5x+4)=7+(2x-3) | | -5x+4(-3+3)=-192 | | x^2*y-3*x*y=0 | | 5(2a+4)=6a-4 | | 1.2m=.6 | | (x^2-5x-3)(x^2-5x-5)=3 | | -x+6x-9=0 | | 2y=-10x+4 | | -7=9x+16-10 | | 2(x+p)=3(6p-x) | | 9k-3k=30 | | 3y+4=y+18 | | -44-1x=28-4x | | x-7.1=-6.2 | | -(3y+1)-(-2y-7)=2 | | 96-2x=43x+16 | | 7(7x-3)+10x= | | 2x+80=158 | | 5p-3=32 | | 3x=3x+2 | | x=.4+(-.2y) | | B-2+6B=27 | | 3x/4=6 | | 6x-11x+4=0 | | 13x^2+1-[7(x^2-8)+5]= | | 6x^7-18x^4+24x^6= | | 6+2y-2=9y+13-6y | | 14(t-3)+4t=6(3t+3)-10 | | 2x-5=x+7+2x | | 5fg+g^2=0 | | 2x+-.5=-.75 | | 5fg+g^2=03 |

Equations solver categories